Recent Progresses in Electrochemical Carbon Dioxide Reduction on Copper‐Based Catalysts toward Multicarbon Products. (26th June 2021) - Yu, Jinli; Wang, Juan; Ma, Yangbo; Zhou, Jingwen; Wang, Yunhao; Lu, Pengyi; Yin, Jinwen; Ye, Ruquan; Zhu, Zonglong; Fan, Zhanxi
Abstract: Electrochemical carbon dioxide reduction reaction (CO2 RR) offers a promising way of effectively converting CO2 to value‐added chemicals and fuels by utilizing renewable electricity. To date, the electrochemical reduction of CO2 to single‐carbon products, especially carbon monoxide and formate, has been well achieved. However, the efficient conversion of CO2 to more valuable multicarbon products (e.g., ethylene, ethanol, n ‐propanol, and n ‐butanol) is difficult and still under intense investigation. Here, recent progresses in the electrochemical CO2 reduction to multicarbon products using copper‐based catalysts are reviewed. First, the mechanism of CO2 RR is briefly described. Then, representative approaches of catalyst engineering are introduced toward the formation of multicarbon products in CO2 RR, such as composition, morphology, crystal phase, facet, defect, strain, and surface and interface. Subsequently, key aspects of cell engineering for CO2 RR, including electrode, electrolyte, and cell design, are also discussed. Finally, recent advances are summarized and some personal perspectives in this research direction are provided. Abstract : The electrochemical reduction of carbon dioxide (CO2 ) to high‐value multicarbon (C2+ ) products is of great significance in creating a carbon‐neutral society. Catalyst engineering and fuel cell engineering are two of the most important strategies to modulate the activity, selectivity, and stability of copper‐based catalysts in CO2 reduction toward the C2+ products.